The recognition of cultural water requirements in the montane rivers of the Snowy Mountains, Australia. Issue 3 (3rd July 2019) - Williams, Simon; Connolly, Dianne; Williams, Alice
ABSTRACT: The cultural importance of water to the Aboriginal people of the Snowy Mountains is significant. Water is integral to healthy waterways, resource availability, and cultural practices that form customs and belief systems. Although there was previously no comprehensive formal legal mechanism to specifically account for cultural water in the water governance arrangements, the authors document the initial restorative healing process for establishing cultural water management in the Snowy Mountains. We identify the four pillars of restorative healing in cultural water management as (1) respect, (2) recognition, (3) representation, and (4) responsibility and self-determination. The inclusion of cultural requirements in water management in the Snowy Mountains of NSW was undertaken by interviewing Aboriginal elders of five communities that have a direct connection to these waterways. Our discussions and management resulted in (1) the establishment of interim cultural water objectives, (2) the cultural naming of high flow releases to the waterways, (3) ceremonies on country associated with the high flow releases, (4) engagement and input to annual release strategies and (5) amendment of the legislative instrument to provide Aboriginal elders representation in future water management.